Study and Microbiologic Analysis of Klebsiella spp. Isolated from Urinary Tract Infections Clinical Samples in Kirkuk City: Studi dan Analisis Mikrobiologi Klebsiella spp. yang Diisolasi dari Sampel Klinis Infeksi Saluran Kemih di Kota Kirkuk - Hussein, Rakan A.; Aziz, Fatema W. Abdul (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Klebsiella pneumoniae is a prevalent cause of urinary tract infections (UTIs), which are a serious issue of public health. Since K. pneumoniae strains are developing increasing resistance to antibiotics, prompt and precise diagnosis is necessary for successful treatment. Aim: The purpose of this study was to separate and recognize K. pneumoniae from UTI patients' samples of urine. Additionally, it aimed to assess the efficacy of several diagnostic techniques, such as Vitek 2, biochemical, and phenotypic. Method: The study, which included both governmental and commercial healthcare facilities, was carried out in Kirkuk province, Iraq, between January and October of 2024. Urine samples were taken from 90 UTI patients, representing both sexes and an extensive range of age groups. The study used various diagnostic techniques. For initial identification, phenotypic and biochemical testing were conducted. The automated Vitek 2 system provides quick and precise identification. Results: 33.4% of the urine samples had K. pneumoniae. The age range of 5 to 25 years old had the highest prevalence, and girls were more likely than males to have it. All of the diagnostic methods used in the investigation were successful in confirming every isolate. Conclusion: The study concluded that K. pneumoniae had a major role in the investigated group's UTIs. The results stress the importance of utilizing a variety of techniques for diagnosis in order to accurately and promptly identify this disease, This is necessary for both infection prevention and successful treatment. Highlights: pneumoniae increasingly causes UTIs and resists antibiotic treatment. Urine samples tested using phenotypic, biochemical, and Vitek 2 methods. 4% positive; young females most affected; all methods effective.. Keywords: Klebsiella pneumonia, Phenotypic Identification, Urinary Tract Infections (UTIs), Biochemical Tests.